Relationship between citizenship behavior and adaptive performance with organizational loyalty of nurses working in Valiasr hospital in Borujen - Mostafa Roshanzadeh; Atefeh Begie; Ali Tajabadi; Samaneh Dehghan Abnavi; Somayeh Mohammadi (Tehran University of Medical Sciences, 2021)
Background & Aim: Nurses' organizational loyalty to health systems plays an important role in expanding organizational performance. Investigating the role of factors such as citizenship behaviors and adaptive performance can be helpful in this regard. The aim of the present study was to investigate the relationship between citizenship behavior and adaptive performance with organizational loyalty in nurses. Methods & Materials: This descriptive, cross-sectional study was conducted in 2019 on 200 nurses working in Valiasr hospital affiliated to Shahrekord University of Medical Sciences in Borujen, and were selected by the random sampling method. A demographic information form, the Lee & Allen's citizenship behavior questionnaire, the Charbonnier-Voirin and Roussel's adaptive performance scale, and the Kumar and Shekhar's organizational loyalty questionnaire were used to collect the data. The data was analyzed by descriptive and inferential statistical tests using the SPSS software version 16. Results: The Pearson's correlation coefficient indicated a significant positive correlation between citizenship behavior and adaptive performance with organizational loyalty (P<0.05). Regression tests showed that citizenship behavior (ADJ.R2=0.199) and adaptive performance (ADJ.R2=0.131) significantly predicted organizational loyalty. All dimensions of citizenship behavior and some dimensions of adaptive performance such as creativity, learning efforts and job stress management can predict organizational loyalty in nurses. The average scores for citizenship behavior (66.85±18.26), adaptive performance (68.76±16.98) and organizational loyalty (120.67±24.09) were reported to be moderate. Conclusion: Managers and planners should pay attention to factors such as creativity, stress management, and continuing education along with improving healthy working relationships and nurses' participation, which can play an important role in expanding organizational loyalty through the development of citizenship behavior and adaptive performance.